Progressivism Philosophy Synthesis for Character Education Reconstruction in Indonesian Curriculum: Sintesis Filsafat Progresivisme untuk Rekonstruksi Pendidikan Karakter dalam Kurikulum Indonesia - Nurfauziah, Astri; Herlambang, Yusuf Tri; Mulyati, Tita (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Moral degradation among elementary school students in the era of globalization has raised concerns about the alignment between character education goals and curriculum practices. Specific Background: In Indonesia, character education has been formally integrated into the 2013 Curriculum and the Independent Curriculum as part of national educational reform. Knowledge Gap: However, the implementation of character education often remains administrative and symbolic, while classroom practices still emphasize cognitive assessment rather than experiential moral development. Aims: This study examines the philosophy of progressivism as an analytical framework for reconstructing character education within Indonesian curriculum policy. Results: Through qualitative literature analysis and comparative philosophical examination of Dewey, Neill, Lickona, and Freire, the study finds that progressive principles such as reflective learning, dialogical interaction, and experiential participation are partially reflected in national curriculum design. The Independent Curriculum shows a stronger progressive orientation than the 2013 Curriculum, yet its implementation remains constrained by teacher preparedness, institutional culture, and assessment systems. Novelty: This study proposes a synthesis of classical progressivism and critical pedagogy to construct a holistic–reflective model of character education. Implications: The proposed framework supports the development of reflective, experience-based, and socially aware character education within Indonesian curriculum reform. Highlights • Progressive principles appear in Indonesian curriculum policy but rarely shape classroom practice• Independent Curriculum introduces experiential and participatory moral learning structures• Dewey–Freire theoretical synthesis frames reflective and socially aware character formation Keywords Progressivism Philosophy; Character Education; Indonesian Curriculum Policy; Critical Pedagogy; Moral Education